2016
DOI: 10.1136/bjsports-2016-096579
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and factors associated with preparing for competing in the heat: a cohort study at the 2015 IAAF World Athletics Championships

Abstract: PurposeAssess exertional heat illness (EHI) history and preparedness in athletes competing in a World Athletics Championships under hot/humid conditions and identify the factors associated with preparedness strategies.MethodsOf the 207 registered national teams invited to participate in the study, 50 (24%) accepted. The 957 athletes (49% of all 1965 registered) in these teams were invited to complete a precompetition questionnaire evaluating EHI history, heat stress prevention (heat acclimatisation, precooling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
127
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(139 citation statements)
references
References 36 publications
4
127
5
Order By: Relevance
“…It is unsurprising therefore, that repeated steady‐state exercise during consecutive day HA, do not appear to be widely embraced by competitive athletes (Périard et al. ). Prescribing TDHA and specifically afternoon sessions, may also increase HA efficiency as time spent at the desired isothermic T re of >38.5°C was extended during afternoon compared to morning sessions (+14 vs. +6 min); yet ∆ T re were lower (+1.3°C vs. +1.6°C), thus requiring less exercise time to reach target temperatures due to circadian rhythm and higher resting T re .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unsurprising therefore, that repeated steady‐state exercise during consecutive day HA, do not appear to be widely embraced by competitive athletes (Périard et al. ). Prescribing TDHA and specifically afternoon sessions, may also increase HA efficiency as time spent at the desired isothermic T re of >38.5°C was extended during afternoon compared to morning sessions (+14 vs. +6 min); yet ∆ T re were lower (+1.3°C vs. +1.6°C), thus requiring less exercise time to reach target temperatures due to circadian rhythm and higher resting T re .…”
Section: Discussionmentioning
confidence: 99%
“…Medium‐ (MTHA: 10–14‐days) and long‐term (LTHA: >14‐days) protocols which maximize adaptations exacerbate these challenges, a factor which may provide some explanation as to why, in spite of clear recommendations from the scientific community, only ~15% of athletes undertook HA prior to competition in heat stress (Périard et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are likely reasons for only 15% of athletes undertaking a recognised HA intervention prior to the IAAF World Championships, in spite of hot climates being forecast (Periard et al 2017). A proposed method for inducing (should access to an environmental chamber not be possible), or enhancing the efficiency (by accelerating the attainment of necessary physiological stimuli for adaptation) of HA is the wearing of clothing/garments which restrict heat loss during exercise (Dawson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Among athletes participating at the World Athletics Championships, Périard et al 7 recently reported that approximately half of the athletes participating in the study had previously experienced heat illness symptoms (eg, cramping, severe headaches). However, only 15% of them reported having prepared specifically for the championships by undertaking heat training regimens 7…”
Section: Pay Attention To Climatic Conditionsmentioning
confidence: 99%